Psychiatric and Psychosocial Concerns in HIV Treatment (Out of Print) - Lara Stepleman; Ralph Gillies; Jackie London (Association of American Medical Colleges, 2007)
Abstract Becoming infected with HIV and taking medications to delay the development of AIDS not only affect one's physical well-being but also significantly impact one's personal relationships, cognitive functioning, and emotional state. Clinicians working with patients with HIV can improve their patients' health outcome and quality of life by knowing and addressing psychosocial and psychiatric concerns commonly associated with HIV and HIV treatment. These include medication side effects, treatment complexities, cognitive impairment, patient disclosure to partner(s), drug use, and depression, as well as many other concerns. This module describes these issues and provides examples of assessment strategies and interventions to assist in care. Video lectures, case examples, role-plays, test items, and resources are provided to enhance learning. The content has been presented to first-year medical students and second-year family medicine residents at the Medical College of Georgia. Medical student learners had more questions about HIV and AIDS in general, as well as questions about the ethics of protecting others. Resident learners had more questions about medication side effects, identifying cognitive problems, and maximizing treatment adherence. Many institutions do not have an expert who can provide educational information on HIV, AIDS, and the impact of treatment on an individual, so this module presents evidence-based information along with case examples to personalize the disease. Clinicians who complete this module will have greater knowledge of the psychosocial aspects of HIV and AIDS and, as a result, improve their care of patients.